"Have Car, Can Travel": Journalistic Practice, Oil Entanglements and Climate Reportage in Aberdeen, Scotland. Issue 1 (2nd January 2022) - Hinde, Dominic
Abstract : This article recounts the practice of producing a commercial newspaper feature for a major American outlet on energy transition and the end of the oil boom in Aberdeen, Scotland. Speaking to both media and energy geographies, it pursues journalistic practice as a form of energy ethnography, exposing how entangled journalism practitioners are with the systems they report with reference to the concept of petroculture. Narrating 48 hours spent on the ground in the oil city, it discusses the invisible processes behind the commercial publication of a transition narrative and the experience of working in the field to construct the story. By focusing on questions of transnational power and gatekeeping, the concept of the energy city, and the role of oil in both visible and invisible forms, it uses its unique dual practitioner/academic perspective to speculate on the possibility of moving beyond market friendly "good news" transition narratives to more meaningful interrogations of energy.